Resolução de problemas: um problema ou um mero exercício nas escolas públicas do interior da paraíba? - Silva, Isaías Pessoa da. (2012)
This research aimed to make an analysis of how students solve mathematical problems in the classroom in the city of Serra da Raiz, Paraíba. The survey was conducted with a class of 9th grade of elementary school of the State School for elementary and high school Maria Jose Miranda Burity in the city of Serra da Raiz. We chose some theorists argue that resolution of problems in the classroom to support our discussions as Polya (1995), Pozo (1998), Dante (2000, 2002), Smole and Diniz (2001), Lester (1983) and Van de Walle (2009). The methodology was qualitative, descriptive and analytical. The main instrument for data collection used in this study was a semi-structured survey applied to 11 students. The method for data analysis was a simple case study, only interaction with the data. At the end of this study we found that most students could not read or interpret questions, many students had difficulty differentiating a simple exercise of direct application in a formula with a problem situation. We believe that more thought is needed about what is teaching and learning mathematics in school environments. That the content and activities are offered to students consistent with their own region, especially when we use the problem solving in pursuit of developing autonomy, critical thinking and reflective of these students so that they can trace their own resolution strategies, many times making mistakes but also hitting, and thus building their own learning.